From mega-events hosting to scientific leadership: A seven-decade scientometric analysis of pioneer countries - Sajad Gholampour; Behzad Gholampour; Alireza Elahi; Alireza Noruzi; Ali Akbar Saboury; Saeed-Ul Hassan; Faran Ahmed; Raheel Nawaz; Sid Terason (Cogent Social Sciences, 2023)
Mega-events have always been an attractive topic for sports management academics. We used scientometric software packages to look at the studies on this topic that have been added to the Web of Science database in the last 68 years. Not only did we give an overview of the background information of the researchers, the status of their collaborations, and the countries and institutions they represented, but we also pointed out active and influential publication sources on this topic. We focused on the Olympic Games and other sports mega-events like the FIFA World Cups, as well as the environmental, tourism, economic, social, political, and cultural aspects of these events. We also made a list of the countries, organizations, and scholars who have made important contributions to the field. Researchers in sports management and sporting event hosts can both use this study as a guide for their own work.